2020
DOI: 10.1002/mds.28182
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment Is More Common in Parkinson’s Disease and Is a Risk Factor for Poor Health Outcomes

Abstract: Background Visual impairment is associated with hip fracture, depression, anxiety, and dementia in the general population, and many causes of visual impairment are preventable or treatable with early detection. However, the prevalence, outcomes, and healthcare utilization patterns associated with visual impairment have not been examined in Parkinson’s disease (PD). Methods We performed a cross‐sectional analysis of all Medicare beneficiaries with complete data in 2014 and longitudinal analysis of beneficiaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
(84 reference statements)
2
20
0
Order By: Relevance
“…Early involvement of visual dysfunction is interesting—particularly so because it precedes retinal abnormality and the earliest cortical neurodegeneration. This is consistent with emerging data that suggest visual changes are an early manifestation or even a precursor of cognitive change in Parkinson’s disease ( Williams-Gray et al , 2013 ; Anang et al , 2014 ), including some of our own work on the discovery cohort ( Leyland et al , 2020 ) and more recently showing, in very large cohorts, that Parkinson’s disease patients with poor vision have a worse phenotype with higher rates of dementia ( Hamedani et al , 2020 ; Han et al , 2020 ). Together, this evidence suggests the exciting prospect that routine assessment of vision may have a role in disease stratification for cognitive decline in Parkinson’s disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Early involvement of visual dysfunction is interesting—particularly so because it precedes retinal abnormality and the earliest cortical neurodegeneration. This is consistent with emerging data that suggest visual changes are an early manifestation or even a precursor of cognitive change in Parkinson’s disease ( Williams-Gray et al , 2013 ; Anang et al , 2014 ), including some of our own work on the discovery cohort ( Leyland et al , 2020 ) and more recently showing, in very large cohorts, that Parkinson’s disease patients with poor vision have a worse phenotype with higher rates of dementia ( Hamedani et al , 2020 ; Han et al , 2020 ). Together, this evidence suggests the exciting prospect that routine assessment of vision may have a role in disease stratification for cognitive decline in Parkinson’s disease.…”
Section: Discussionsupporting
confidence: 89%
“…The event-based model would also be of interest applied to dementia with Lewy bodies or established Parkinson’s disease dementia. As visual processing deficits are seen in the prodromal phase of dementia with Lewy bodies ( McKeith et al , 2020 ) and in patients with more rapid Parkinson’s disease dementia ( Anang et al , 2014 ; Hamedani et al , 2020 ), we predict that visual changes will also be found as early events in Lewy body dementia.…”
Section: Discussionmentioning
confidence: 98%
“…Both take advantage of established clinical databases with secure PD diagnoses and accurate measures of visual function captured in their relative populations. 6,7 These studies highlight 2 distinct and clinically relevant aspects of visual dysfunction in PD: (1) that loss of visual function may be found at the very earliest stages of PD, a kind of early nonmotor sign, and (2) that visual dysfunction in established PD is a marker of poor prognostic outcomes.…”
mentioning
confidence: 99%
“…The risk of dementia is markedly increased in Parkinson's disease (PD) but its onset and severity is highly heterogeneous 1,2 , making individual-level predictions difficult and limiting timely therapeutic interventions. There is now a growing body of evidence that Parkinson's patients with visual dysfunction are at a greater risk of dementia [3][4][5] , but whether this translates into structural change over time is not yet known.…”
Section: Introductionmentioning
confidence: 99%